A Remote Access Laboratory for Electrical Circuit Experiments - Gustavsson, Ingvar (Dublin : TEMPUS Publications, 2003)
Many laboratory experiments in electrical engineering courses can be performed remotely using real equipment in a laboratory. Traditional circuit theory experiments have been conducted over the Internet at Blekinge Institute of Technology (BTH) in Sweden using the same experimental set-up from different locations simultaneously. The circuits are formed using remotely controlled switch matrices. The instruments and switch matrices used are computer-based PXI (PCI Extensions for instrumentation) devices which have virtual front panels that can be displayed on a remote PC. This approach is neither a simulation nor a SCADA (Supervisory Control and Data Acquisition) application. The students control the instruments in the same way as they would in a local laboratory. The only difference is that they do not form the circuits and connect the test probes manually. These laboratory experiments have been used successfully in undergraduate engineering education at BTH and at Luleå University of Technology, Sweden using a lab server at BTH. Two transducer laboratory exercises are also available for more experienced students, who mostly welcome the chance of doing the experiments from home at any convenient time. These exercises contain comparatively slow mechanical movements allowing only one user to be logged on and controlling the experiments at once. Video transmission is provided so other users can follow what is happening and also perform parts of the experiments.